PERFORMANCES OF SOME APPLICATIONS IN PASSIVE OPTICAL NETWORKS - Catalbas, Cenk; Unverdi, N. Ozlem (IEEE, 2014)
In this study, some passive optical network structures are investigated. Characteristic properties of passive optical network technology types APON, BPON, EPON, GPON and GEPON are explained The topology of a reliable optical communication system is formed with OptiSystem 12.0 simulation program and the simulation results are interpreted. The performances of BPON and GPON technologies are evaluated.
Keywords: Engineering; Telecommunications